Impact of entrepreneurial orientation and firm performance: the moderating role of social media in the Maldives tourism industry context - Waheed, Ahmed (2023)
The Maldives tourism industry's SMEs face significant challenges, such as limited resource access, an extremely competitive market, and a need for technological infrastructure. However, to gain a competitive edge and overcome these challenges, entrepreneurial orientation has been identified as a potential driver of competitive performance. A study was conducted to investigate the correlation between entrepreneurial orientation and firm performance in the Maldives tourism industry, while also exploring the potential moderating effect of social media usage on this relationship. Collecting 157 Maldives guest house samples their data was analyzed using PLS-SEM structural equation modeling. The findings indicate that guest house enterprises must adopt an entrepreneurial mindset and leverage social media effectively to enhance their firm's performance. Doing so can improve their resource acquisition, market reach, customer engagement, feedback-driven learning, and agility. The results highlight the importance of incorporating entrepreneurial orientation and utilizing social media resources and capabilities in the tourism industry to enhance firm performance. It also underscores the pivotal role of hospitality managers in competitive strategy, considering the information-intensive hospitality service demands their attention. The notes suggest that policymakers should prioritize the development of an entrepreneurial culture and utilize social media to promote creativity and boost small and medium-sized enterprises. This highlights the significance of supporting SMEs to drive progress and innovation.